ANALISIS TEMPERATUR PELAT LANDASAN HOT-GAS WELDING DAN BENTUK BEVEL TERHADAP KEKUATAN TARIK LASAN HDPE - Kris Witono; Agus Setiawan; Sugeng Hadi Susilo (Jurnal Energi dan Teknologi Manufaktur, 2022)
Welding has developed rapidly at this time, both for metallic and non-metallic materials, one of the methods used for plastic welding is Hot-Gas Welding. Plastic is a very difficult material to weld due to its low thermal conductivity. The quality of the mechanical properties of the existing plastic welded joints is not close to the strength of plastic objects without welding. The purpose of this study was to determine the effect of variations in the temperature of the base plate and variations in the shape of the bevel during the Hot-Gas Welding process on the tensile strength of HDPE sheet welded joints, to determine the conditions of the interaction between variations in the temperature of the base plate and variations in the shape of the bevel during the Hot-Gas Welding process. HDPE sheet welded joints that produce maximum tensile strength values. In this study, two independent variables were used, namely the base plate temperature (30,70,110,150 C), variations in bevel shape (V, X, U) and three controlled variables which included HDPE plastic material with a thickness of 5mm, using added filler material in the form of HDPE plastic with a diameter of 4 mm and a hot gun airflow heating temperature of 250℃. The tensile test standard uses the ASTM D 638-03 standard and for data processing is done by DOE factorial, as supporting data macrostructural photos of each weld joint are carried out. The results showed that the maximum tensile strength of HDPE welded joints was obtained at the temperature of the base plate of 150°C and the V bevel shape with a value of 18.46 MPa or 84.22% of the parent material